EFFECTIVENESS OF TRAINING POWER AND PLANING SERVING TECHNIQUES IN YOUNG VOLLEYBALL PLAYERS (Physical Culture and Sport: Scientific Perspective, 2025)
Today, volleyball training is characterized by a variety of program material and a wide range of exercises. The relevance of the topic lies in the fact that serving is one of the main and most spectacular techniques for winning a volleyball game. In our opinion, this topic is subject to additional study and attracts the interest of fans of physical activity.This issue has not received enough attention in the scientific and methodological literature devoted to the problems of modern volleyball. First of all, this is due to the specifics of technical techniques in volleyball, the effectiveness and quality of which are quite difficult to assess in comparison with other sports, where specific measurable results are used for this purpose (for example, time, distance, weight). Various scientists have repeatedly attempted to create a methodology for a certain assessment, which was based on indicators of pedagogical observations of the game, combined by a single system of coding, recording and mathematical processing of information.The study of scientific and methodological literature proves the insufficient use of various physical exercises to increase the effectiveness of the planing serve, the serve in the jump, in the training process of young volleyball players. Our work is related to research in this direction, which determines its relevance.To practically substantiate the effectiveness of the use of special exercises for teaching the serving technique in a team of young volleyball players in the training process of a volleyball team, we conducted a pedagogical experiment.The experiment was conducted from November to December 2024 on the basis of the ODYUSSH in Lutsk. 30 young volleyball players from the training group of the fourth year of study, aged 12-13 years, participated in the experiment. As a result of this work, the levels of formation of basic serving skills in volleyball were identified. The duration of one lesson in groups is 2 academic hours, 4 times a week. Systematic (at least 2 times a year) medical control was carried out, after which all players were allowed to participate in the training process and competitions.Two groups of girls were formed, which were distinguished by the uniformity of results: 15 girls in the 1st experimental and 2nd experimental groups. Both teams fulfilled the regulatory requirements for special physical training, as well as the simplest elements of technique.In the 1st experimental group, classes were held according to the coach's work plan, working on teaching the power serve technique (jump serve). And in the educational and training process of the 2nd experimental group, the gliding serve technique was used.So, we can conclude that the physical fitness indicators in both groups of girls increased significantly. Namely, the girls of the 1st experimental group increased their jumping performance, this is due to the repeated performance of jumping exercises, which were used in the training process to improve the power serve technique.In the 2nd experimental group, strength indicators, hand dynamometry and stuffed ball throws are higher - this is also the result of these special exercises that were carried out in the educational and training process of the gliding serve technique. The "shuttle" run in both groups that were part of the pedagogical experiment does not differ significantly, since both teams performed exercises for speed and endurance in the same amount during training.
Keywords: volleyball; serves; girls; training; technique